Ultra-dispersive monolayer graphene oxide as water-based lubricant additive: Preparation, characterization and lubricating mechanisms. (March 2021) - Gan, Chaoliang; Liang, Ting; Li, Xiaopeng; Li, Wen; Li, Hao; Fan, Xiaoqiang; Zhu, Minhao
Abstract: Although graphene oxide (GO) is deemed as an admirable lubricant additive to enhance the tribological properties of water, there remain great challenges in improving its dispersion stability and re-dispersity in water, and understanding the effects of dispersity and exfoliation degree on lubricity of GO. Herein, the functionalized GO (GO-EmimN(CN)2 ) with extraordinary dispersity, re-dispersity and high exfoliation degree is successfully prepared using 1-ethyl-3-methyl imidazolium dicyanamide as intercalator of multilayer graphene oxide (MGO). GO-EmimN(CN)2 as water-based lubricant additive dramatically decreases the wear rate and wear width of GCr15 steel by 74% and 40% compared to pure water, 53% and 45% to MGO respectively. Finally, lubricating mechanisms of GO-EmimN(CN)2 are determined and proposed via abundant surface analysis techniques. Graphical abstract: Image 1 Highlights: Functionalized monolayer graphene oxide (GO-EmimN(CN)2 ) is successfully synthesized using a facile method. GO-EmimN(CN)2 shows ultra-high dispersity and re-dispersity as water-based lubricant additive. GO-EmimN(CN)2 dramatically decreases the wear rate and wear width of GCr15 bearing steel by 74% and 40% compared to pure water, 53% and 45% to traditional multilayer graphene oxide. Lubricating mechanisms of GO-EmimN(CN)2 have been determined and proposed via abundant surface analysis techniques.